2023
DOI: 10.3892/etm.2023.11910
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives in hypospadias research: A scoping review of articles published in 2021 (Review)

Abstract: Hundreds of papers are written about hypospadias every year referring to all aspects of the pathology, being one of the most common congenital malformations. The present study conducted a scoping review of articles published in 2021 to present the main issues and summarize current perspectives and achievements in the field. It searched for the keyword 'hypospadias' in the three most popular databases (PubMed, Scopus and Web of Science). After the analysis of the publications, they were categorized into differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 273 publications
0
7
0
Order By: Relevance
“…These data can provide a more personalized experience by providing age, gender, date of birth, and date of surgery. They can tailor their content and recommendations to meet specific user needs 16,34–36 . The results of this study showed that demographic information, such as date of birth and date of surgery, is essential from an expert's perspective for the necessary personalization of the application.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…These data can provide a more personalized experience by providing age, gender, date of birth, and date of surgery. They can tailor their content and recommendations to meet specific user needs 16,34–36 . The results of this study showed that demographic information, such as date of birth and date of surgery, is essential from an expert's perspective for the necessary personalization of the application.…”
Section: Discussionmentioning
confidence: 93%
“…To ensure proper care and support for children during the postoperative period, having a well‐designed practical educational application for caregivers is essential 34 . This application should encompass all key aspects of caring for a child with congenital hypospadias after surgery, including physical care, treatment follow‐up, and practical considerations 35 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As hypospadias can have a wide range of severity, more than 250 different techniques have been described to date. A review of the literature shows that TIP, first described by Snodgrass, is still the most commonly used technique in the treatment of distal hypospadias, with MAGPI, hybrid Mathieu urethroplasty, onlay preputial flap, dorsal inlay graft urethroplasty, and many others mentioned as alternatives [20]. A meta-analysis conducted by Zhang et al, which included 16 studies and compared the postoperative outcomes of 1386 patients operated on with the Snodgrass or Mathieu technique, showed an equal inci-dence of fistulas and wound dehiscence but a higher frequency of meatal stenoses in patients operated on using the Snodgrass technique [21].…”
Section: Discussionmentioning
confidence: 99%